Overview of the population genetics and connectivity of sea turtles in the East Asia Region and their conservation implications - Ng, Connie Ka Yan; Ishihara, Takashi; Hamabata, Tomoko; Nishizawa, Hideaki; Liu, Min; Song, Jia-hao; Li, Tsung Hsien; Fong, Chia-Ling; Moon, Dae Yeon; Kim, Il Hun (Frontiers in Marine Science, 2024)
Understanding the current status and recent development of the population genetics and connectivity of sea turtles is crucial for effective conservation management of the species. Five sea turtle species, green turtle (Chelonia mydas), loggerhead turtle (Caretta caretta), hawksbill turtle (Eretmochelys imbricata), olive ridley turtle (Lepidochelys olivacea) and leatherback turtle (Dermochelys coriacea), are recorded in the East Asia Region situated in the western side of the North Pacific Ocean. We compiled information from 35 published genetic studies on the five sea turtle species, with a focus on green turtle and loggerhead turtle, which are the most studied species (in 30 studies) in view of their commonness and occurrence of nesting populations. We provided an overview of the key methods and findings of these previous studies, addressing two main objectives on genetic structure of the rookeries and their differences compared to other populations, and connectivity of the rookeries and foraging aggregations. By identifying information gaps and conservation needs, we discussed future developments for sea turtle genetic studies and conservation implications in the region.